Practice of multidisciplinary team collaboration and nursing of a patient undergoing surgery for colon cancer (1例结肠癌手术患者多学科协作护理体会) - WANG Nannan (王楠楠); WANG Yutao (王玉涛); LIU Yunchao (刘云超); GUO Lian (郭连); ZHANG Yi (张依); SU Guohua (苏国华); PENG Yujie (彭雨洁) (Association of Integrative Nursing, 2023)
To explore the experience of multidisciplinary team collaboration in the treatment and postoperative nursing of a patient with colon cancer. According to the characteristics of the patient's disease, multidisciplinary consultation was used to formulate the operation plan preoperatively. The nursing group also organized various professional teams to conduct nursing evaluation, formulated the corresponding nursing plan, and provided professional and standardized nursing interventions on body position management, catheter maintenance, nutrition support and exercise guidance. The multidisciplinary team model can accelerate the postoperative rehabilitation process of the patient with colon cancer (本文总结1例结肠癌手术患者多学科团队协作护理体会。针对患者疾病特点, 采用多学科联合会诊制定手术方案和护理措施, 术前完善检查、做好宣教, 术后给予体位护理、管路护理、营养指导、锻炼指导等护理干预, 以加速患者康复并提高患者满意度。)